The morphology of the pulp chamber floor of permanent mandibular first and second molars in an Indian subpopulation—a descriptive cross-sectional study employing Pawar and Singh classification - Pawar, Ajinkya M.; Singh, Shishir (PeerJ, 2022)
Background Mandibular molars are multi-rooted teeth with a complex and strenuous root canal anatomy. Because there is relatively negligible literature describing the pulp chamber floor anatomy, predicting the exact anatomical layout and its variations is daunting. A thorough comprehension and knowledge of the same is required for efficacious endodontic treatment consequence. The purpose of this study was to characterise and ascertain the pulp chamber floor anatomy of permanent mandibular first (ManFMs) and second (ManSMs) molars in an Indian population. Methods On 2,134 extracted human mandibular first (ManFMs = 1,067) and second molars (ManSMs = 1,067), a descriptive cross-sectional investigation was executed. Cleaning and removal of hard and soft tissue debris were performed, followed by flattening the anatomical crown until the pupal architecture was uncovered. A stereomicroscope with a magnification of 4.5 magnification was used to investigate the pulpal anatomy. Statistical analysis was carried out using chi square test, with 95% confidence intervals and a p value of 0.05 considered statistically significant. Results The majority of the ManFMs showed presence of three canal orifices in 57.73%, followed by four orifices 31.31%, five orifices 8.81%, and six orifices 2.15%. For ManSMs, majorly three orifices were found in 39.83% specimens, followed by two orifices in 37.39%, four orifices in 16.31%, and single root canal orifice was observed in 6.47%. The mesio-buccal, mesio-lingual, disto-buccal, disto-lingual canal orifices exhibited round and oval shapes in both ManFMs and ManSMs. The shape was predominantly oval with a single distal canal orifice (84.25% ManFMs and 74.16% ManSMs). In ManSMs, among the single root canal orifice, 66.66% were round in shape and 33.34% were C-shaped. In ManSMs with two root canal orifices, mesially 79.44% exhibited oval and 20.56% round shape. Distally, 74.16% were oval and 25.84% were round. The shapes of the access cavities for ManFMs were rectangular in 46.67% and triangular in 53.33%. For the ManSMs, the access cavities were triangular in 39.83%, rectangular in 16.31% and non-classified (others) in 43.86% of specimen. In both ManFMs and ManSMs, the pulp chamber floor morphology was predominately Y shaped (57.73% and 39.83%) according to the Pawar and Singh classification© of pulp chamber floor anatomy. Conclusion Our study indicated that the orifices on the pulp chamber floor are arranged in a typical manner, supporting the proposed categorization. Furthermore, description of the anatomical patterns of the pulp chamber guides the clinicians in chair-side treatment decisions.
Keywords: Canal orifices; Mandibular molars; Morphology; Pawar and Singh classification©; Pulp chamber floor anatomy